Application of The Computational Semi-Empirical Method in Calculating The Fission Yield with Reference to The JENDL Data - rizal kurniadi (Institut Teknologi Bandung, 2022)
Fission Yield calculation techniques can be completed in various ways. In this work, other calculation techniques will be described. Namely, a semi-empirical technique that utilizes random numbers. This semi-empirical method can produce fitting parameters to obtain other physical quantities. Because it uses a random number initiator, computations can be completed in parallel. Therefore, the computation time is shorter. This paper will show in sequence the steps of this technique. The calculation begins by assigning a value to the incident energy and random position of the nucleons, and then ends after fission products occur. This paper only describes the process of calculating the Fission Yield for several U isotopes.